Earthgazing VR experience to help astronauts cope with loneliness (2021)
3.11.2021 - Research aimed at helping astronauts deal with isolation and confinement could also have an impact on those back on Earth suffering from COVID-related loneliness. Researchers in Simon Fraser University's iSpace Lab have created a virtual reality experience-called Earthgazing-which will be tested as part of SIRIUS 2021 , a study launching Nov.
Keywords: mediaCoverage; proj--SIRIUS-earthgazing-newscoverage